Effects of environmental factors and management practices on microclimate, winter physiology, and frost resistance in trees - Charrier, Guillaume; Ngao, Jérôme; Saudreau, Marc; Améglio, Thierry (Frontiers in Plant Science, 2015)
Freezing events are one of the most important limiting factors determining the ecological distribution and production of tree species. Assessment of frost risk, is therefore, critical for forestry, fruit production and horticulture. Frost risk is substantial when hazard (i.e., exposure to damaging freezing temperatures) intersects with vulnerability (i.e., frost sensitivity). Based on a large number of studies on frost resistance and frost occurrence, we highlight the complex interactive role of environmental conditions (e.g., light, temperature), carbohydrates, and water status in frost risk development. To supersede the classical empirical relations used to model frost hardiness, we propose an integrated ecophysiologically-based framework of frost risk assessment. This framework details the individual or interactive roles of these factors, and how they are distributed in time and space at the individual level (within-crown and across organs). Based on this general framework, we are able to highlight factors by which different environmental conditions (temperature, flood, drought) and management practices (pruning, thinning, girdling, sheltering, water aspersion, irrigation and fertilization) could influence frost sensitivity and frost exposure of trees.